Impact of soil erosion on water treatment cost: Case of Gihira water treatment plant, Rubavu, Rwanda - Vincent, Nsanzumukiza Martin; Niwenshuti, Emmanuel; Justin, Nzayinambaho; Athalie, Mukankusi; Theoneste, Sindikubwabo (International Journal of Geography and Geology, 2023)
The study aimed to assess the impact of soil erosion on cost of Gihira Water Treatment Plant (GWTP). Raw water and treated data were gathered from GWTP in different seasons (rain and dry season). The parameters such as TSS, Turbidity and E.coli were determined with standard methods. Documentary review was used to collect data related to annual rainfall, elevation, soil texture, land use and vegetation cover. The results revealed that heavy rainfall impacted negatively quantity of water produced at GWTP with rate of 6.8%, 10.80% and 6.67% in March, April to May and1.57%, 1.73% and 1.66% in June, July and August in 2017. In 2018, the rates of 12.09%, 5.57% and 4.76% in March, April and May and the rates of 1.81%, 1.09% and 1.93% in June, July and August were recorded. The same situation was reproduced in 2019, where the rates were 8.09%, 4.76% and 4.76% in rain season against of 1.38%, 0.85 and 0.55% of dry season. The findings revealed that a high disturbance of the water treatment occurred during the rainy season due to agriculture practices and high steep slope of the areas which lead to high rate of soil erosion in the catchment and more chemicals were used to treat potable water than in dry seasons.